2020
DOI: 10.1177/2192568220912993
|View full text |Cite
|
Sign up to set email alerts
|

Shape Loss of Autoclaved, Machine-Bent Cobalt-Chrome and Titanium Spine Surgery Rods

Abstract: Study Design: This was a biomechanical study. Objective: Shape loss of surgical spine rods has been implicated as a factor leading to postsurgical loss of alignment correction. Our objective was to compare the degree of shape loss in surgical spine rods of different compositions under physiological conditions that were bent before or after being autoclaved.Methods: 10 CoCr and 10 commercially pure titanium (CPTi) surgical spine rods were contoured using a machine press. Five CoCr and 5 CPTi rods were bent befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Due to its higher Young’s modulus (~210 GPa) [ 30 ] than titanium, CoCr spinal rods more effectively stabilize the spine and correct abnormalities of spinal curvatures such as scoliosis [ 96 , 98 , 99 ]. In the study by Willson et al [ 100 ], CoCr rods demonstrated the least amount of shape loss in a radius of curvature compared with commercially pure titanium rods throughout the study.…”
Section: Mechanical Characteristics Of the Most Frequently Used Metal...mentioning
confidence: 99%
“…Due to its higher Young’s modulus (~210 GPa) [ 30 ] than titanium, CoCr spinal rods more effectively stabilize the spine and correct abnormalities of spinal curvatures such as scoliosis [ 96 , 98 , 99 ]. In the study by Willson et al [ 100 ], CoCr rods demonstrated the least amount of shape loss in a radius of curvature compared with commercially pure titanium rods throughout the study.…”
Section: Mechanical Characteristics Of the Most Frequently Used Metal...mentioning
confidence: 99%